Correlations of production factors in automated milking system in a Hungarian dairy farm - Hlel, Nawel; Holló, Gabriella; Bus, Bence; Süli, Ágnes; Nyúl, Zsófia; Szabari, Miklós Gábor (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2024)
Nowadays the use of automated milking systems (AMS) is increasingly popular as a technology that can reduce labor, increase milk production, and maximize profit. This study, which was carried out on a private dairy farm located in West Hungary, aimed to examine the relationship between AMS and production efficiency in lactating cows with herd sizes ranging from 267 to 322 Holstein-Friesian cows in the middle of lactation specifically 165 ± 10 days in milk. The result of this study indicates that on average, an AMS unit milked 49 ± 3 cows daily with each cow being milked 2.7 ± 0.1 times per day and producing a daily milk yield of 32.5 ± 1.3 kg per cow. The data was statistically analyzed using Pearson correlations and multiple linear regression analysis. The study found that daily milk yield was positively correlated with milking frequency (r = 0.61, p < 0.01) and negatively correlated with failed milkings (r = - 0.34, p < 0.01) but had no correlation with refusals (p > 0.05). As we expected, a positive correlation was observed between the amount of concentrate offered in AMS per cow per day and both milk yield (r = 0.52, p < 0.01) and milking frequency (r = 0.27, p < 0.01). Finally, the fat content was negatively correlated with daily milk yield (p < 0.05) and the amount of concentrate, however, there was no correlation observed for protein content with daily milk yield or the amount of concentrate in the AMS (p > 0.05). Detailed knowledge of these factors such as milking frequency and concentrate intake associated with increasing milk yield by using AMS will help guide future recommendations to producers for maximizing milk yield and decreasing the cost on dairy farms.